PERAN KEPERCAYAAN MEMEDIASI PERSEPSI RISIKO TERHADAP NIAT MENGGUNAKAN MANDIRI MOBILE BANKING DI KOTA DENPASAR - Jayantari, Ida Ayu Agung Upadianti; Seminari, Ni Ketut (E-Jurnal Manajemen; Vol 7 No 5 (2018)DO - 10.24843/EJMUNUD.2018.v07.i05.p13, 2018)
Risk perception is an influential factor in a person's intention to use a product. Companies should consider factors that can minimize the perception of these risks, one of which is trust. This study wishes to explain the role of confidence in mediating the perception of risk to the intent of using. This research was conducted in Denpasar City involving 100 respondents. Data collection method used is purposive sampling. Data collection was done by distributing questionnaires. Furthermore, data from the results of collecting questionnaires processed by using the validity test, and reliability test to determine the feasibility and consistency of indicators in the questionnaire. In addition, another test is conducted path analysis (path analysis) and Solimun Theory. The results of the study found that the perception of risk had a negative and significant effect on the intention of using. While trust has a positive and significant effect on the intention of using. So it can be said that to increase the intention of using can be done by minimizing risk perception and foster trust.